2020
DOI: 10.1096/fj.202000085r
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific effects of high‐fat diet on cognitive impairment in a mouse model of VCID

Abstract: Half of all dementia patients have evidence of vascular contributions to cognitive impairment and dementia (VCID), either as a single pathology or as a multi-etiology dementia, 1 yet, there remains a severe lack of knowledge regarding VCID. Type 2 diabetes is a major risk factor for VCID, as it is known to cause damage to the cerebral vasculature and blood brain barrier (BBB). 2-4 Furthermore, there is a sex difference in risk for VCID that varies by metabolic status. While most studies agree that in a nondiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 68 publications
8
39
0
Order By: Relevance
“…We found that unilateral carotid artery occlusion surgery (MxD mice) caused deficits in cerebral blood flow in the cortical surface that persisted 4 months after surgery. This is in line with our previous work, and that of others, documenting prolonged deficits in blood flow in the ipsilateral hemisphere (19,(42)(43)(44)58). While we observed the expected effect of MxD to cause hypoperfusion, we did not observe any sex or diet differences.…”
Section: Neuropathology Findingssupporting
confidence: 93%
See 3 more Smart Citations
“…We found that unilateral carotid artery occlusion surgery (MxD mice) caused deficits in cerebral blood flow in the cortical surface that persisted 4 months after surgery. This is in line with our previous work, and that of others, documenting prolonged deficits in blood flow in the ipsilateral hemisphere (19,(42)(43)(44)58). While we observed the expected effect of MxD to cause hypoperfusion, we did not observe any sex or diet differences.…”
Section: Neuropathology Findingssupporting
confidence: 93%
“…For example, we have shown that HF diet impairs adult hippocampal neurogenesis in female, but not male mice (18). Further, we recently found that HF diet in middle aged mice causes a wider array of cognitive deficits in females compared to males (19). Others have found that a HF diet in the 3xTg-AD model of AD exacerbates cognitive impairment (20)(21)(22)(23)(24)(25) and AD pathology such as brain atrophy (20), inflammation (22,26), and Aβ load (26)(27)(28).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The effect of metabolic disease on VCID risk is even greater for women compared to men. In line with this clinical data, using mouse models of metabolic disease (chronic high fat diet) and VCID (chronic cerebral hypoperfusion), we have found that high-fat diet causes greater metabolic impairment and a wider array of cognitive deficits in middle-aged females compared to males [37]. We have found that metabolic disease severity is more strongly associated with white matter damage, astrogliosis [38], and reduced neurogenesis [39] in females compared to males.…”
Section: Kristen L Zuloagasupporting
confidence: 72%